Aqua-"culture" : - Genschick, Sven (LIT, 2014)
This book considers the interplay of subjective and objective structures on the practices in Pangasius cultivation. It shows that economic dependencies in a global commodity production system have led to a transformation process that most aquaculturists cannot cope with. The discrepancy between the ideal and real situation can no longer be ignored otherwise the downward trend will continue.